2002
DOI: 10.1536/jhj.43.675
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Angiotensin-converting Enzyme Inhibitor Enalapril on Sympathetic Neuronal Function and .BETA.-adrenergic Desensitization in Heart Failure after Myocardial Infarction in Rats.

Abstract: SUMMARYOne of the beneficial effects of angiotensin-converting enzyme (ACE) inhibitors in the treatment of heart failure may derive from sympathoinhibition and the prevention of β-adrenergic desensitization. However, the roles of these properties in the overall effects of ACE inhibitor are not clear. We studied the effects of chronic enalapril treatment (20 mg/L in drinking water for 12 weeks) on left ventricular (LV) function, cardiac norepinephrine (NE), sympathetic neuronal function assessed by 131 I-metaio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…6 Previous studies have suggested that ACEI, angiotensin receptor blocker, -blockers and spironolactone can improve the parameters of cardiac 123 I-MIBG scintigraphy and decrease plasma levels of BNP in patients with CHF. 16,23,[25][26][27][28][29][30][31][32][33][34][35][36] Both parameters of cardiac 123 I-MIBG scintigraphy and plasma BNP levels are useful surrogate markers for the management of CHF patients. We have reported that repeated measurements of cardiac 123 I-MIBG imaging parameters before and after 6-month optimized treatments are useful for predicting the prognoses of patients with moderate to severe CHF.…”
Section: Discussionmentioning
confidence: 99%
“…6 Previous studies have suggested that ACEI, angiotensin receptor blocker, -blockers and spironolactone can improve the parameters of cardiac 123 I-MIBG scintigraphy and decrease plasma levels of BNP in patients with CHF. 16,23,[25][26][27][28][29][30][31][32][33][34][35][36] Both parameters of cardiac 123 I-MIBG scintigraphy and plasma BNP levels are useful surrogate markers for the management of CHF patients. We have reported that repeated measurements of cardiac 123 I-MIBG imaging parameters before and after 6-month optimized treatments are useful for predicting the prognoses of patients with moderate to severe CHF.…”
Section: Discussionmentioning
confidence: 99%